Elite athletes and media appearances: opportunity or obligation?. Issue 7 (2nd July 2020) - Kovacs, Agnes; Doczi, Tamas
Abstract: In the new era of communication, enormous changes have occurred in how and why things get publicity. Elite athletes are involved in this process; but they diverge in the extent they would like to be part of it. The objective of this article is to examine Hungarian Olympic athletes regarding their perspectives towards publicity. For an in-depth understanding of Olympians' attitudes towards the media, in the research, they were divided into three groups: media refrain, neutral and media friendly. The results indicate that there are significant differences between the three groups in many dimensions. Older athletes are more likely to be media friendly, while gender differences can be marked in less openness among female athletes. However, members of all three categories mentioned that they would like to read quality publications about themselves – including their profession – and try to avoid exposing their private life and be part of scandals.